Outdoor human environments : the changing face of climatic barriers to soft mobility and gathering in winter communities - Larsson, Agneta; Chapman, David (Luleå tekniska universitet, Hälsa och rehabilitering, 2018)
Introduction: In Arctic regions, generations have evolved lifestyles that fit with working and living with local conditions and seasonal variations. With emerging climate changes new risks appear and prior individual experiences based on preconceptions of risk may not remain valid. In everyday life, soft-mobility is required in varying conditions, such as ice and snow covered surfaces, darkness, extreme weather conditions. Inability to detect environmental clues to risk is a critical aspect for injury. Also, fear and activity avoidance lead to an increased risk of physical inactivity, a significant population health concern worldwide. Methods: An explorative survey, on subjective ratings of barriers to 1) soft mobility and 2) the use of outdoor public space in winter was performed. The EAMQ –Climate survey, tailored for climatic sensitive urban design research, include dimensions of distance, ambient and terrain, and a range of weather conditions found in winter, such as sun, coldness, wind, ice and ground surface properties (ice, snow, slush). Respondents were 1) 344 people in Northern Sweden, and 2) 361 people in Canada and Scandinavia. Results: The results highlight that rain, icy surfaces and darkness are today’s most significant barriers to soft-mobility in winter. For the use of outdoor public spaces, the most significant barriers were slushy and icy surfaces, rain precipitation and darkness. Conclusions: The traditional risks associated with outdoor activity in winter are changing with climate change. Future urban design and planning for safer and more walkable winter cities need to consider a more extensive pallet of weather conditions. Poster presentation. Abstract will be included in the abstract book